Southern storm Sherman's march to the sea - Trudeau, Noah Andre 1949-
Award-winning Civil War historian Trudeau has written a fascinating new history of Sherman's legendary and devastating march through Georgia. Told through diaries and letters of Sherman's soldiers, this work paints a vivid picture of an event that changed the course of America